2013
DOI: 10.1007/s00405-013-2798-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined type IIIB with bilateral type I thyroplasty for pitch lowering with maintenance of vocal fold tension

Abstract: Objective To evaluate type IIIB thyroplasty using the excised larynx bench apparatus and determine how altering vocal fold contour by performing bilateral medialization of the inferior vocal fold affects phonation. This procedure could be performed in patients for whom pitch lowering is desirable, such as female-to-male transsexuals or male patients with mutational falsetto in whom intensive voice therapy was insufficient. Methods Aerodynamic, acoustic, and high-speed videokymographic data were collected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Less invasive modifications were proposed by Kocak et al and Tucker. 5, 6 Hoffman et al 14 proposed the combination of thyroplasties, for example, shortening thyroplasty with bilateral medialization thyroplasty. Kocak et al 5 reported 21 patients undergoing a window anterior commissure relaxation laryngoplasty, including one patient with mutational falsetto.…”
Section: Discussionmentioning
confidence: 99%
“…Less invasive modifications were proposed by Kocak et al and Tucker. 5, 6 Hoffman et al 14 proposed the combination of thyroplasties, for example, shortening thyroplasty with bilateral medialization thyroplasty. Kocak et al 5 reported 21 patients undergoing a window anterior commissure relaxation laryngoplasty, including one patient with mutational falsetto.…”
Section: Discussionmentioning
confidence: 99%
“…57 In a subsequent study, an excised canine larynx was used to evaluate type IIIB thyroplasty combined with bilateral type I thyroplasty for lowering pitch while maintaining the tension of the vocal folds. 58 Thompson et al modified the approach of medialization thyroplasty by performing medialization thyroplasty via the subthyroid cartilage approach on an excised canine larynx, showing that it is possible to improve acoustic and aerodynamic parameters without requiring to make a window on thyroid cartilage. 59 Lagier et al used ImageJ to measure the mean glottal area of 21 excised human larynges in the situations of no adduction, arytenoid adduction, membranous vocal fold adduction, and both arytenoid and membranous adduction.…”
Section: Simulations Of Clinical Applicationsmentioning
confidence: 99%